Treatment of Children with Immune Thrombocytopenia by High Dose Intravenous Dexamethasone: A Window for Improvement - Ali Hadi Mahdi (Journal of Global Pharma Technology, 2018)
Introduction Immune thrombocytopenia is a hematological disorder Characterized by platelet destruction caused by auto antibodies resulting in reduction in platelet count to lower than normal range and increased bleeding tendency. Corticosteroids are considered one of the most appropriate treatment options for pediatric ITP. Methods: In this study 16 pediatric patients with acute ITP had been enrolled to evaluate their response to high pulsed dose of dexamethasone given as a 4-day course every 14 days for 4 courses by measuring their platelet counts before and after each course and along 14 months after completing the 4 courses. Results: There was a significant (p<0.0001) increase in platelet count after each cycle in comparison with platelet count before the same cycle. All the patients, at the end of fourth cycle, showed either partial or complete response and no one showed minimal or no response. Conclusion: High dose dexamethasone can be proposed as a first-line treatment for children with ITP. Repeated cycles of therapy seem to be more efficient than only one cycle to achieve a long-term response.